Genetics of salt tolerance in rice - Sankar, Deepa (Research in Plant Biology, 2015)
Experimental procedures viz., line x tester analysis, diallel analysis and stability analysis have been utilized in rice breeding programs to study combining ability, heterosis, gene action and stress tolerance capacity of various genotypes based on yield related traits.Ã‚Â The results have helped in development of good varieties and hybrids. Excessive work is available in the particular area of research as many plant breeders in Asia work towards improving the yield of rice. A review on gene action studies in rice has been attempted with emphasis on the research progress made in India.